Comparison of mutational profiles and clinical outcomes in patients with acute myeloid leukemia with mutated RUNX1 versus acute myeloid leukemia with myelodysplasia-related changes with mutated RUNX1. Issue 6 (11th May 2020) - Nguyen, Lynh; Zhang, Xiaohui; Roberts, Evans; Yun, Seongseok; McGraw, Kathy; Abraham, Ivo; Song, Jinming; Braswell, Diana; Qin, Dahui; Sallman, David A.; Lancet, Jeffrey E.; List, Alan F.; et al.
Abstract: Studies comparing the prognostic role of RUNX1 mutations ( RUNX1 mut ) in acute myeloid leukemia (AML) and acute myeloid leukemia-with myelodysplasia-related changes (AML-MRC) are limited. Our study examines the genetic profile of 118 RUNX1 mut AML patients including 57 AML with RUNX1 mut and 61 AML-MRC with RUNX1 mut and 100 AML, NOS patients with wild type RUNX1 ( RUNX1 wt ). Results revealed that AML-MRC patients with RUNX1 mut had shorter median overall survival (OS) (11 ± 3.3 months) when compared to AML with RUNX1 mut (19 ± 7.1 months) and AML, NOS with RUNX1 wt (not reached) ( p = .001). The most common concurrent mutations observed in AML-MRC with RUNX1 mut patients were DNMT3A, SRSF2, ASXL1, and IDH2 while in AML with RUNX1 mut patients were ASXL1, SRSF2, TET2, IDH2, and DNMT3A . ASXL1 and TET2 mutations appeared to adversely affect OS in AML-MRC, but not in AML with RUNX1 mut . Concurrent RUNX1/DNMT3A mutations, in contrast had negative impact on OS in AML with RUNX1 mut, but not in AML-MRC with RUNX1 mut .